Impact of the Balanced Scorecard on the competitiveness of SMEs: a systematic review of international literature between 2019 and 2024 - Uribe Suárez, David (2025)
This article presents a systematic review of the literature on the impact of the Balanced Scorecard on the competitiveness of small and medium-sized enterprises (SMEs). A search was conducted in several well-known academic databases such as Scopus, ScienceDirect, Springer, and Semantic Scholar, using the keywords Balanced Scorecard AND SME AND Competitiveness to identify studies published between 2019 and 2024, using the PRISMA methodology. Thirty-five articles were selected, with a focus on data to create an index ordered in Scopus and classified in Q1 and Q2 quartiles. These studies show a positive effect of the BSC on key variables such as financial performance, customer satisfaction, internal process optimization, and, to a lesser extent, market positioning. Thus, successfully implementing the BSC in SMEs requires contextual adaptations due to their strategic needs and specific resource constraints.